The Factors that Affects Corporate Liquidity of Manufacturing Firms in Malaysia: Evidences from Twenty Manufacturing Firms - Murthy, Uma; Anthony Mariadas, Paul; Sinniah, Suguna; Perumal, Gopal; Nadarajan, Dineswary (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to find and measure how and to what extend firm size, net working capital, and leverage and cash flow influence corporate liquidity holdings in Malaysia. The study selected 20 manufacturing companies listed in bursa Malaysia (ten top manufacturing companies and ten random manufacturing companies), for the purpose of investigating the relationship between variables as well as for the purpose of comparing the result of the top manufacturing companies and random manufacturing companies. Five years financial data from 2013 to 2017 was selected for the study. Four factors were selected in this study which are firm size, leverage, net working capital and cash flow. The finding of this research had investigated that there the relationship between corporate liquidity of top manufacturing companies and all variable is not significant. However, the results of the random manufacturing firms had indicated that firm size and cash flow are found to be significantly related to corporate liquidity. While, the remaining two factor of random manufacturing companies which are leverage and net working capital are discovered to have insignificant relationship with corporate liquidity.